Students' Responses to Plot Device of Going/Trapped to Another World Seen in The Wonderful Wizard of Oz by Frank L Baum: Reading Interest and Popular Culture Knowledge - Sandika, Edria; Rizano, Gindho; Resna, Nabilah Dzakirah (Vivid: Journal of Language and Literature, 2023)
This study discusses the plot device of ‘going/trapped to another world’ as seen in The Wonderful Wizard of Oz by Frank L. Baum about reading interest and popular culture knowledge by the students’ responses from the English Department Universitas Andalas. It aims to find the correlation between their knowledge and interest in the plot device of ‘going/trapped into another world’ and the popularity of the Isekai genre among them. The result shows that the majority of the respondents were familiar with and interested in the genre, and the genre’s ability to facilitate imaginative escapism, served as coping mechanism from real life challenges, it helps their opinion that the plot device remains popular and relevant in the future with strong confidence in its enduring appeal as relatable experiences become the primary reason for its popularity to stay in the pop culture world.